Realizing sustainable rural tourism through Community-Based Tourism (CBT): A SWOT analysis of Curug Dhuwur Waterfall - Sari, Ita Novita (Jurnal Bisnis Kehutanan dan Lingkungan, 2024)
Background: This study focuses on the development strategy of community-based tourism (CBT) at Curug Dhuwur Waterfall in Wanarata Village. Village tourism showcases the uniqueness of village life, including social characteristics, natural beauty, and culture, which have the potential to attract visitors. Local community involvement is a key factor in the sustainability of rural tourism. Method: Descriptive qualitative and field study methods were used. The data comprises primary and secondary sources. The research results were analyzed using SWOT Analysis to determine effective strategies for tourism development. Findings and Conclusion: The analysis concludes that the tourism development strategy should leverage SWOT Analysis to maximize strengths and opportunities while minimizing weaknesses and threats. The implementation of this strategy includes optimization and training in tourism management, maintaining the natural environment, promoting tourist areas, improving infrastructure, raising community awareness of sustainable tourism, organizing comparative studies for managers, and enhancing cooperation with the district government and related departments. This research aims to contribute to the development of community-based tourism in Wanarata Village. Novelty/Originality in this article: This study presents a new model in rural tourism development by combining SWOT analysis and community-based tourism (CBT) principles. This study offers a framework that can be adapted for developing other rural tourism destinations, combining environmental conservation, local economic empowerment, and cultural preservation.